INOVASI SEHAT UNTUK ANAK DALAM MINUMAN TEH TARIK JELLY DAUN KELOR SEBAGAI UPAYA PENCEGAHAN STUNTING ANAK PRA SEKOLAH DI DESA PILANGPAYUNG - Suryani; Siti Nurul Istiqomah; Mira Saida Putri; Anitya Novi Widyaastuti; Linda Listiyaningrum; Indra Gunawan; Fitria Jaya Wicaksana; Firli Mareta Salamah; Febryana Nur Khafifah; Festy Mahanani Mulyaningrum; Meity Mulya Susanti; Wahyu Riniasih; Jayanti Dwi Puspita (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2025)
Background: Stunting or growth failure in children remains a serious health issue in Indonesia. The prevalence of stunting among children under five years old was 21.6% in Indonesia in 2022, down from 24.4% in 2021. There are plants that contain very high levels of nutrients, from macronutrients to micronutrients, which are beneficial for public health. One such plant is Moringa oleifera, commonly known as the moringa tree.Objective: The aim of this community service project is to increase knowledge about the management of stunting.Method: The community service activity was carried out through a public health counseling session in the village, which took place on February 4, 2025.Results: The results of the implementation showed an improvement in the respondents' knowledge, with 88 respondents (93.3%) categorized as having adequate knowledge, and a decrease in the category of insufficient knowledge, with only 2 respondents (6.7%).